2006
DOI: 10.1385/bter:109:1:025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Coenzyme Q10 on Catalase Activity and Other Antioxidant Parameters in Streptozotocin-Induced Diabetic Rats

Abstract: Although coenzyme Q10 (CoQ10) is a component of the oxidative phosphorylation process in mitochondria that converts the energy in carbohydrates and fatty acids into ATP to drive cellular machinery and synthesis, its effect in type I diabetes is not clear. We have studied the effect of 4 wk of treatment with CoQ10 (10 mg/kg, ip, daily) in streptozotocin (STZ)-induced (40 mg/kg, iv in adult rats) type I diabetes rat models. Treatment with CoQ10 produced a significant decrease in elevated levels of glucose, chole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 26 publications
4
42
0
5
Order By: Relevance
“…This may decreases TG and VLDL Levels (Suckling and Jackson, 1993). It has been proven that consuming of CoQ10 for 4 weeks significantly reduces the serum levels of triglycerides, total cholesterol, low density lipoprotein cholesterol (LDL) and very low density lipoprotein cholesterol (VLDL) and increases HDL in streptozotocin induced diabetic rats (Modi et al, 2006). It is provided; high fat feeding impairs glucose-induced insulin secretion only in the context of chronic hyperglycemia in Goto-Kakizaki rat islets.…”
Section: Resultsmentioning
confidence: 99%
“…This may decreases TG and VLDL Levels (Suckling and Jackson, 1993). It has been proven that consuming of CoQ10 for 4 weeks significantly reduces the serum levels of triglycerides, total cholesterol, low density lipoprotein cholesterol (LDL) and very low density lipoprotein cholesterol (VLDL) and increases HDL in streptozotocin induced diabetic rats (Modi et al, 2006). It is provided; high fat feeding impairs glucose-induced insulin secretion only in the context of chronic hyperglycemia in Goto-Kakizaki rat islets.…”
Section: Resultsmentioning
confidence: 99%
“…Modi et al (2006a) reported that Coenzyme Q10 significantly decreased the lipid peroxidation which may be due to decreased oxidative stress. Also, Modi et al (2006b) showed that Coenzyme Q10 treatment reduced lipid peroxidation and increased antioxidant parameters like superoxide dismutase, catalase and glutathione in the liver homogenates of diabetic rats. Coenzyme Q10 supplementation was associated with significant reduction in thiobarbituric acid reactive substances, malondealdehyde and diene conjugates in coronary artery disease patients, indicating an overall decrease in oxidative stress (Singh and Niaz, 1999).…”
Section: Discussionmentioning
confidence: 96%
“…The reduction in lipid levels and increase in HDL-C levels may be due to inhibition of LDL-C oxidation and reduce oxidative stress. Moreover, Modi et al (2006a;2006b) showed that the treatment with Coenzyme Q10 produced significant decreases in the elevated levels of serum cholesterol, triglycerides, VLDL-C, LDL-C and atherogenic index and increased HDL-C levels in diabetic treated rats. However, the mechanism by which Coenzyme Q10 lowered serum triglycerides is not clear but it may be possible due to either a decrease in VLDL-C synthesis or channeling of VLDL-C to pathway other than to LDL or an increase in lipoprotein lipase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Krizman et al (2012) recorded nearly 10% lower cholesterol concentration in heart tissue of broilers when supplemented with CoQ10. The CoQ10 supplementation decreased plasma total cholesterol concentration in humans (Cicero et al, 2005) and rats (Modi et al, 2006). The CoQ10 was reportedly able to suppress the hepatic cholesterogenesis in rats (Omkumar et al, 1992) and in hens .…”
Section: Coenzyme Q10 On Lipid Metabolismmentioning
confidence: 93%
“…The CoQ10 reduced cholesterol metabolism in the plasma of patients with myocardial infarction (Singh et al, 2003) and in diabetic rats (Modi et al, 2006). The CoQ9, a major coenzyme Q in rats, decreases plasma total cholesterol concentration and suppresses hepatic cholesterogenesis (Krishnaiah and Ramasarma, 1970).…”
Section: Coenzyme Q10 On Lipid Metabolismmentioning
confidence: 99%